2019
DOI: 10.1192/bjp.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

High- versus low-intensity interventions for perinatal depression delivered by non-specialist primary maternal care providers in Nigeria: cluster randomised controlled trial (the EXPONATE trial)

Abstract: BackgroundContextually appropriate interventions delivered by primary maternal care providers (PMCPs) might be effective in reducing the treatment gap for perinatal depression.AimTo compare high-intensity treatment (HIT) with low-intensity treatment (LIT) for perinatal depression.MethodCluster randomised clinical trial, conducted in Ibadan, Nigeria between 18 June 2013 and 11 December 2015 in 29 maternal care clinics allocated by computed-generated random sequence (15 HIT; 14 LIT). Interventions were delivered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(142 citation statements)
references
References 27 publications
(55 reference statements)
6
135
1
Order By: Relevance
“…We did a total of 6 Focus Group Discussions (FGDs) with three mothers groups (n=17), and three primary care providers groups (n=25) between 6 th March and 29 th April 2018. In the RCT, our team trained non-specialist maternal and child health clinicians (MCHC) to deliver psychosocial interventions for perinatal depression using the Nigerian adapted WHO mhGAP intervention guide (mhGAP-IG) (Gureje et al, 2019). The 17 mothers who were adolescents when the RCT was conducted, were no longer adolescents at the time of the FGDs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did a total of 6 Focus Group Discussions (FGDs) with three mothers groups (n=17), and three primary care providers groups (n=25) between 6 th March and 29 th April 2018. In the RCT, our team trained non-specialist maternal and child health clinicians (MCHC) to deliver psychosocial interventions for perinatal depression using the Nigerian adapted WHO mhGAP intervention guide (mhGAP-IG) (Gureje et al, 2019). The 17 mothers who were adolescents when the RCT was conducted, were no longer adolescents at the time of the FGDs.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of PD among adolescents complicates their unique ageand development-related challenges and thus demands services attuned to the unique needs of this age group. Evidence from Nigeria suggests that children of adolescent mothers with depression have poorer outcomes (Oladeji et al, 2019). However, Nigeria, like other low resource nations of the region, lacks adequate numbers of trained care providers as well as appropriate infrastructure to support high quality primary maternity care for adolescents (WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In a recently concluded cluster randomized controlled trial of interventions for perinatal depression in primary care in Oyo State, Nigeria [15], we had a chance to do some explorations of what an appropriate intervention for adolescents with perinatal depression might consist of in order for it to meet the complex and unique needs of this group of mothers. In that trial, 772 teenage adolescents (aged ≤ 19 years; mean age 18 years) were among the entire sample of 9352 persons screened for perinatal depression in the second or third trimester (that is, 8.3% of the entire sample).…”
Section: Background and Rationalementioning
confidence: 99%
“…Following the meetings, key informant interviews were held with frontline maternal care providers and with adolescent mothers. The key informants were selected from among providers and adolescent trial participants in our previously concluded RCT [15]. In the interviews with providers, we explored facility manpower and workload issues; experience with the delivery of treatment during the RCT, in particular engagement with the adolescents; and facility organizational issues, including those relating to the scheduling of clinic appointments for trial participants.…”
Section: Data Collection Procedures Formative Studymentioning
confidence: 99%
See 1 more Smart Citation